ALTERNATIVE HYBRID CONTROL OF SWITCHED SYSTEMS. AN APPLICATION TO MACHINE DC FED BY MULTICELLULAR CONVERTER (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
In this article, we present an alternative of hybrid control, where we choose as an actuator, the DC motor controlled by a multi-cellular converter. For this, a switching control for the multi-cellular converter is established, to provide the proper reference value for the regulation of the speed by using the Petri nets. We consider a converter with three cells which is represented as a hybrid system with eight modes of operation. The operation modes of the system are governed by the adjustable reference voltage and a reference speed, which are calculated by means of an energy balance principle. Simulation results are given in order to illustrate the performance of such a method. To show the validity of our approach, a practical implementation based on  Spartan 3E FPGA resulted.
Keywords: Hybrid control; Floating condensers; Multicellular converter